In order to overcome crime in economy, there have been several related statues. The success of a statue to reach the goals, it really depends on the criminal law policy contained in the statues. In fact criminal law policy in the statues relates to econom - Firman Muntaqo (Faculty of Law, Universitas Diponegoro, 2011)
Until now, regulation and land law policy on plantation not to realize the aim of UUPA yet. Even, the plantation farmer be marginalized to labors on the plantation, and be the landless. Economically, The farmer is very depending on the Plantation Corporation (state, national private corporation, joint venture although foreign corporation that have facilitated by the government) that have land widespread. The New Order Regime implemented capitalistic politic with classical capitalist paradigm, and authoritarian for reach high economic growth fastly. It's caused be injustice for the people. Land deconstruction on plantation is a way to bring justice for the people, especially for the farmer plantation by giving access to be land plantation owner. Kata kunci: Dekonstruksi Hukum Pertanahan, Perkebunan